Liberté, égalité, fraternité: Changing erroneous conceptions of continuous assessment - Kamanga, E.; Lubbe, A.; Annandale, M.; Reyneke, M. (South African Journal of Higher Education, 2025)
Scholars agree that assessment drives teaching and learning, which highlights the fact that the purpose of assessment is to enhance learning. In the framework of self-directed learning (SDL), the benefit of assessment for learning is promotion of SDL skills, such as critical thinking. Yet, data gathered from staff and students from a university’s education faculty during the first semester of 2023 (after three years of implementing continuous assessment) suggest that staff and students have distorted perceptions of continuous assessment and continue to struggle with it. Instead of being able to freely utilise the opportunity to promote learning in their respective disciplines, lecturers seem to be burdened by constraining programmes of assessment and administration, while students experience continuous assessment as nothing more than the challenge to complete multiple summative tasks, mostly in written form. This paper addresses misconceptions about continuous assessment in education. With the correct conceptual understanding comes the freedom to manage and facilitate assessment in diverse disciplines, to realise students’ critical thinking skills. We aim to demonstrate what is possible across the faculty, to set a common goal of excellence in assessment, and to foster enthusiasm for exploring possibilities in training innovative teachers. The participants completed one open-ended questionnaire aimed at gauging their assessment literacy. We share the findings that emerged from data analysis that involved assigning codes using ATLAS.ti™.